Creating a new Medina state power, Islam, and the quest for Pakistan in late colonial North India - Dhulipala, Venkat (Cambridge University Press, 2016)
Discusses the fundamental assumptions regarding the foundations of Pakistani nationalism as well as our current understanding of the roots of its postcolonial identity crisis.